Compression Splices of Reinforcing Bars in Reactive Powder Concrete - Hussein Al-Quraishi; Mahdi Al-Farttoosi; Raad Abdulkhudhur (Salehan Institute of Higher Education, 2019)
Compression splices are widely used in compression members such as columns in multi- story buildings. There are efficient design equations for compression splice of reinforcement embedded in conventional concrete proposed by design codes of practice. However, there is no design equation for compression splice in compression members made of reactive powder concrete (RPC). So, it is required to introduce a design equation to calculate the steel bars lap splice length of RPC compression members. In this study, an experimental work was conducted to investigate the effect of different variables on compression splices strength. These variables were compressive strength of concrete, transverse reinforcement amount, splice length, yield stress of reinforcement and spliced rebar diameter. The experimental results showed that; Increase in the yield stress of reinforcing bars, length of spliced bars and compressive strength of concrete result in increasing in splice strength. Meanwhile, increase in diameter of reinforcing bars result in decreasing in compression splice strength. The increase in the amount of transverse reinforcement has insignificant effect on compression spliced strength of rebar. Finite element analysis was used to analyze the tested specimens and compared between numerical and experimental result was carried out. The numerical and experimental ultimate load and load-deflection behavior is very close to each other. Finite element method was used to investigate a wide range of experimental variables values through a parametric analysis. A new proposing equation for compression splicing of rebar in RPC column is presented in this research.